Sistem Monitoring Kendaraan Secara Real Time Berbasis Android menggunakan Teknologi CouchDB di PT. Pura Barutama - Ramos Somya (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2018)
PT. Pura Barutama is a company with many production areas. Products that have been produced will be delivered to some destinations using company's vehicles. Those vehicles are managed by Vehicle Unit of PT. Pura Barutama. Based on the research, there is a problem in the term of vehicle tracking and monitoring. The delay of product delivery is often occur for no apparent reason from the drivers. Previously, Vehicle Unit already has a GPS Tracker installed on each vehicle, but this GPS Tracker can only be triggered using SMS to send the location of vehichles. This method causes the lack of tracking and monitoring information obtained by the company. This research developed a new model of tracking and monitoring system based on Android platform. CouchDB technology is also used to provide a real time tracking and monitoring system. The test result shows that this new system has advantages compared with the old tracking system and can be used to replace the old system.